Impact of homeownership on children's academic outcomes: a critical methodological review of literature - Ma'rof, Aini Marina; Redzuan, Ma'rof (Marsland Press, 2012)
The primary goal of this paper is to provide a critical methodological review of literature on homeownership and child academic outcomes. It focuses on the strengths and weaknesses regarding causal inference of different research findings. We first build a conceptual framework on the relations between homeownership and child academic outcomes. In the body of the review, six empirical studies using different quasi-experimental techniques were critically analyzed and compared regarding their strengths and weaknesses of establishing causal inference. A final comment on the quality of literature and future directions are also discussed.